Contrasting carbon and water flux dynamics in an East African rangeland and cropland - Odongo, Vincent O.; Leitner, Sonja; Dowling, T.P.F.; Gluecks, Ilona V.; Jackowicz-Korczynski, M.; Rinne, J.; Wooster, M.J.; Merbold, Lutz (2025)
This study examines carbon (C) and water dynamics in two East African dryland ecosystems: a savanna rangeland grazed by livestock and wildlife, and a rainfed cropland under minimal tillage. Over 185 days, both systems were showed a similar magnitude of C emissions with differing temporal patterns. The rangeland showed fluctuating C exchange, with losses followed by increased C uptake after rainfall events. The cropland initially acted as a C sink, and when lateral C export from chickpea harvest were accounted for, the overall C balance shifted to a net source. Cropland demonstrated higher carbon use efficiency (CUE), driven by efficient C allocation for crop growth, supported by fertilizers, pesticides, and minimum tillage practices. During the peak growing period, cropland also had greater water use efficiency (WUE) likely reflecting optimized agricultural management under favorable moisture conditions. However, over the entire period, WUE was significantly higher in the rangeland than in the cropland (p > 0.05) possibly due to more consistent vegetation cover and adaptive traits that minimize water loss. The cropland showed a complex relationship between WUE and CUE, where increased productivity also simultaneously drove higher respiration rates. Our findings, particularly the shift in cropland carbon balance following harvest emphasize the importance of including lateral C fluxes and intra-annual variations in C balance assessments for accurate budgeting. Both ecosystems were co-limited by water and nitrogen, with plant adaptations to drought and dry spells, including efficient water use and sustained photosynthesis under moisture stress playing a critical role in maintaining ecosystem CUE. Sustainable land management strategies that account for the interactions between C and water dynamics, biodiversity, and ecosystem functioning are vital to enhancing C storage, mitigating climate change, and improving resilience in rangelands and croplands.